Mass spectrometry-based metabolite profiling of wild and in vitro propagated Sabah jewel orchid Macodes limii j.j. wood & a.l. lamb - Devina David (2023)
Jewel orchids are commonly known for their beautiful foliage venations and some of them are appreciated for their remarkable medicinal properties. Macodes limii is a terrestrial jewel orchid endemic to Sabah, which can only be found in specific areas with ultramafic soil. The plant is vulnerable to extinction due to its specific growth requirements, besides unsustainable collection by orchid collectors for trading purposes. Despite its high ornamental value, less effort was given to protect this native species as well as to explore its chemical composition. Therefore, the current study was conducted to establish an in vitro regeneration protocol for M. limii, as well as to decipher the chemical composition of this endemic plant. The results revealed that M. limii can be regenerated via shoot tip and nodal cultures. However, to promote shoot multiplication, nodal explant was superior to shoot tip when cultured on half-MS basal media containing 0.5 mg/L of kinetin or 1.0 mg/L TDZ, which has promoted up to three shoots after 90 days of culture. Meanwhile, the total phenolic and flavonoid contents in the wild and in vitro cultivated M. limii plants revealed a strong positive correlation to the antioxidant potential by DDPH and FRAP assays. The integration of gas chromatography (GC) and liquid chromatography (LC) coupled with mass spectrometry (MS) has profiled the metabolites in the wild and in vitro cultivated M. limii plants that mostly consist of carbohydrates and their derivatives, organic acids, amino acids, fatty acids as well as flavonoids and phenolics compounds. Interestingly, this approach also has detected one potential compound, putatively annotated as 3-hydroxy-4-butanolide, a synonym to kinsenoside, which was previously reported to be the main bioactive compound in other medicinal jewel orchids. In combination with the multivariate statistical analysis, it was revealed that growing environments (wild and in vitro cultivation), as well as the age of plants (9, 18, and 27 months of culture), influenced the chemical composition of M. limii. The obtained results were the first ever reported on the micropropagation protocol as well as the metabolite profiling in M. limii and for the Macodes genus. The establishment of this in vitro propagation protocol is significant in reducing the risk of exploitation of this plant from the wild, and information on the plant metabolite profiles might serve as fundamental in understanding the metabolite variations in jewel orchids.